2017
DOI: 10.20473/jbe.v5i32017.311-324
|View full text |Cite
|
Sign up to set email alerts
|

Snacking At School Increased The Risk Of Overweight/Obesity In Children

Abstract: ABSTRAKObesitas anak merupakan salah satu masalah kesehatan masyarakat yang paling serius pada abad ke-21. Kebiasaan makan yang tidak baik seperti kelebihan makan tinggi lemak, gula, dan kalori serta kurangnya aktivitas fisik menjadi penyebab overweight atau obesitas pada anak. Penelitian ini bertujuan untuk menganalisis hubungan pola konsumsi makanan jajanan dengan kejadian overweight/obesitas. Penelitian dilakukan di SDN Ploso I-172 Kecamatan Tambaksari Surabaya pada bulan Mei-Juli 2017 dengan desain case co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
0
4
0
3
Order By: Relevance
“…12 Another school-based study in Surabaya assessing the snacking pattern and obesity revealed that school children within a month routinely consumed 16 times, 8 times, 12 times, and 16 times of fritters, sausages, a glass of sweetened condensed milk, and other added sugar products, respectively. 13 Studies in the mid-20th century mentioned high-fat products were responsible for the increasing number of people with obesity worldwide. 7,14 The accusation on high-fat products led the global products to promote "less fat" taglines, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…12 Another school-based study in Surabaya assessing the snacking pattern and obesity revealed that school children within a month routinely consumed 16 times, 8 times, 12 times, and 16 times of fritters, sausages, a glass of sweetened condensed milk, and other added sugar products, respectively. 13 Studies in the mid-20th century mentioned high-fat products were responsible for the increasing number of people with obesity worldwide. 7,14 The accusation on high-fat products led the global products to promote "less fat" taglines, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Sekitar 79 juta anak usia dibawah lima tahun di Asia dan Pasifik menderita stunting dan 34 juta anak mengalami berat badan yang kurang, 12 juta diantaranya menderita kekurangan gizi akut dengan peningkatan risiko kematian secara drastis [5]. Anak-anak sekolah dasar merupakan salah satu kelompok yang rawan mengalami gizi kurang diantara penyebabnya ialah tingkat ekonomi yang rendah dan asupan makanan yang kurang seimbang serta rendahnya pengetahuan orang 2 tua [6].…”
Section: Pendahuluanunclassified
“…Akibatnya, anak akan mengalami kelebihan berat badan saat berusia 4-5 tahun [5,14]. Hal ini diperparah dengan kebiasaan mengkonsumsi makanan jajanan yang kurang sehat dengan kandungan kalori tinggi tanpa disertai konsumsi sayur dan buah yang cukup sebagai sumber serat [6,15].…”
Section: Tabel 2 Hasil Screening Status Giziunclassified
“…The pattern of eating that tends to consume fast food is caused by the environment where you live and school. Excessive intake of food and snacks can also result in increased body weight if the variants of snacks are high in sugar, fat, calories, and low in nutrients (Nisak & Mahmudiono, 2017). College students and school-aged youth are also a group of people who tend to be attracted to fast food advertisements on television.…”
Section: The Relationship Between Eating Patterns and Obesity In Stud...mentioning
confidence: 99%